Design and Fabrication of Model of Tesla Coil - Pundlik, Yogesh Yashwant; Pundlik, Gauri Yogesh (Asian Journal of Electrical Sciences, 2019)
This paper discuss the design, fabrication of scaled down of Model of Tesla Coil model for the purpose of explanation to the U.G. students. In Tesla coil gives the high voltage a.c.compared to the DC input to the circuit. The circuit was fabricated. The fabricated coil was tested for breakdown of various solid insulation materials and wireless power transmission.